Mapas dos processos de criação de formatos de programas televisivos: uma proposta metodológica - Tavares, Bruno Rogério (2017)
There is a new panorama of audiovisual content construction that has been opened with the expansion of the TV format formats industry in the world. The emergence and popularization of television can be considered one of the most relevant phenomena in the 20th century in social communication, in the context of Brazilian television productions, the present study aimed to create a methodology for creating new formats of television programs, Based on the analysis of the creative processes used by TV channels, broadcasters and producers, with reference to a new market for the export of audiovisual ideas. This research is justified by the fact that Brazil still has a gap to be filled, since it is not configured as an exporter of television formats. The guiding hypothesis of this research was whether the lack of systematization of the creative process for TV program formats inhibits the development of new ideas for entertainment programs. The hypotheses were also analyzed that the vertical model of the TV stations discourages the development of new projects of formats of programs in Brazil; And that most TV stations do not have creative teams because they do not know how to stimulate or evaluate the creations of new programs. The method used to develop this study was qualitative, using the techniques of exploratory research, bibliography, documentary analysis and cartography, including maps and diagrams. The theoretical framework is based on studies of communication, genres and formats, on theories of genetic criticism, creativity, creative processes, innovation, design thinking and business modeling, as well as the interpretation of data from the Brazilian television scenario. The development of the research finds scientific and methodological support in the line of research Creation Processes in the Media and in the Research Group CCM - Communication and Creation in the Media, aligned with approach of the studies of the professor Lucia Leão